USO DO CLOROFILÔMETRO PARA RACIONALIZAÇÃO DA ADUBAÇÃO NITROGENADA NA CULTURA DO ALGODOEIRO - ALIXAME, Danieli; ZOZ, Jardel; ZOZ, André; QUEIROZ, Ludmila Freitas Marques; STEINER, Fábio (ANAIS DO ENIC, 2017)
-